So, x + y = 42 and y - x = 5;
Then, y = x + 5;
Finally, x + x + 5 = 42;
2x + 5 = 42;
2x = 37;
x = 18.5;
y = 18.5 + 5;
y = 23.5;
Answer:
d. 3
Step-by-step explanation:
hope this helps!!!!!!!<3
Answer:
Step-by-step explanation:
Joint variation has the equation
y = kxz
k is the constant of variation and needs to be solved for using the initial conditions, then filled in later to another equation related to the given info to solve for something else. We are given y = amount of oil used, x = distance traveled, z-squared is the speed. Our equation looks like this, to be exact:
![y=kxz^2](https://tex.z-dn.net/?f=y%3Dkxz%5E2)
Filling in with the initial conditions:
which gives us the
k = .0014166667
Now we need to find the amount of oil used, y, under other circumstances, but this time we have our k.
![y=(.0014166667)(32)(23)^2](https://tex.z-dn.net/?f=y%3D%28.0014166667%29%2832%29%2823%29%5E2)
which gives us that the amount of oil used, when rounded to the tenths,
y = 24.0 barrels
Step-by-step explanation:
(x, y) -> (x+3, y+4)
that is what 3 units to the right (3 units into the outsource x direction) and 4 units up (4 units into the posits y directing) mean.
so, all points go through this translation
(1, 7) -> (4, 11)
(-4, -2) -> (-1, 2)
(-3, 5) -> (0, 9)
Answer:
1. 0=0
2. 0=17
Step-by-step explanation: